CORRELATION BETWEEN THYROID FUNCTION AND OBESITY IN TYPE 2 DIABETES INDIVIDUALS - K, SREEDEVI; A, SRIKANTH; RAO M, PRASAD; P, SAI SEKHAR (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: In the present study, it is aimed to investigate the prevalence of thyroid dysfunction and blood glucose parameters and their correlation in Type 2 diabetes mellitus (T2DM) obese patients. Methods: The present study was a cross-sectional and observational study conducted for a period of 1 year January 2020–January 2022. The patient demographic data, age, and gender were collected from the medical records. After an overnight fast, venous blood samples were collected in the morning for laboratory tests. Electrochemiluminescence immunoassays were used to assess serum free T3 (FT3), FT4, and thyroid stimulating hormone (TSH). Fasting blood glucose, postprandial blood glucose, and random sugar levels were measured using enzymatic method. Body mass index (BMI) was calculated as weight (kg) divided by squared height (m). Results: In the present study, the mean values of thyroid harmones T3, T4 between the obese and non-obese individuals showed that no much significant variations might be due to low sample size. However, the mean values of TSH values were significantly higher 8.7ng/dl for obese individuals than non-obese individuals. There was a significant positive correlation that was identified for thyroid parameters TSH between obese and non-obese T2DM patients. On the other hand, there was a significant influence of postprandial blood sugar, random blood sugar, hemoglobin A1C, and BMI in obese and non-obese T2DM patients and insignificant influence for thyroid parameters T3 and T4. However, the results also showed that there was a highly significant influence of THS levels in obese T2DM patients. Conclusion: The findings of the present investigation showed a high correlation between thyroid function, mainly TSH levels, and Type 2 diabetes, particularly in obese persons.